Peran Guru Akidah Akhlak dalam Mengatasi Perilaku Indispliner Peserta Didik di MTs Tri Bhakti At-Taqwa Lampung Timur - Farkhatin Chamilaini; Ikhwan Aziz Q; M. Sayyidul Abrori (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Discipline is a behavior that shows obedience and obedience to all rules. In moral education,the criteria of right and wrong to judge the actions that appear refer to the Koran and hadith as the highest source of Islamic teachings. Thus, moral education can be regarded as moral education in Islamic education discourse. This research is included in qualitative research. In the course of collecting data the author uses the method of observation, interviews and documentation. As for the research subjects, they included curriculum assistant teachers, Akidah Akhlak teachers and MTs Tri Bhakti At-taqwa students in East Lampung. Meanwhile, in analyzing, the writer used a qualitative descriptive analysis technique. To support the description of the situation in the field, the authors include documentation as a complement and reinforcement of research data. The results of the study show that (1) the concept of learning discipline at MTs Tri Bhakti At-taqwa East Lampung is defined as a form of obedience and obedience of students in carrying out the rules that have been determined by schools and teachers in the learning process because they are driven by the awareness that is in their hearts, this awareness is obtained through exercises. (2) The Aqidah Akhlak teacher plays an active role both outside and inside the class, the way the teacher builds student discipline is by instilling positive values ​​by habituating the General Morals. (3) Supporting factors The teacher's role as an educator is to provide guidance to students what should be done and what should not be done. All of these have been fulfilled, although the process is not yet perfect, both in the teaching and learning process in the classroom and in the school environment.